Groundwater level rise and geological structure influences on land deformation dynamics: insights from managed aquifer recharge operations in Beijing, China - Liu, Shao-Min; Bai, Ming-Zhou (Frontiers in Earth Science, 2024)
Managed Aquifer Recharge (MAR) has been implemented in the upper alluvial plain of the Chaobai River, significantly affecting the groundwater level and causing it to rise. However, the effects of the MAR on land subsidence,remain largely unknown. To elucidate the effects of MAR on land subsidence, a comprehensive analysis was undertaken, integrating interferometric synthetic aperture radar (InSAR) data, extensometer measurements, and groundwater level observations.Our analysis revealed a discernible land rebound phenomenon, with rates escalating from 2.3 mm/a in 2015 to 20 mm/a in 2021. This rebound extends southwestward, following a dispersion pattern that aligns with pre-existing fault structures, suggesting their controlling influence. The groundwater level changes caused by the MAR can cause land rebound, especially near fault footwalls. However,low permeability in fault zones hinders groundwater flow in the hanging wall resulting in slight land deformation. Lithology also affects rebound, with sandy soils showing more significant land rebound, while low-sand areas exhibit limited or delayed rebound. These findings offer crucial insights into the interplay between MAR, groundwater dynamics, and land subsidence in the studied region. They provide a foundation for informed decision-making in groundwater replenishment strategies and precise subsidence prevention and control measures. Future research should maintain a vigilant monitoring of the long-term consequences of MAR on land subsidence to ensure sustainable regional development.